2017
DOI: 10.1016/j.jtho.2016.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Targeting MET in Lung Cancer: Will Expectations Finally Be MET?

Abstract: The mesenchymal epithelial transition factor receptor (MET) is a potential therapeutic target in a number of cancers, including non-small cell lung cancer (NSCLC). In NSCLC, MET pathway activation is thought to occur via a diverse set of mechanisms that influence properties affecting cancer cell survival, growth, and invasiveness. Preclinical and clinical evidence suggest a role for MET activation as both a primary oncogenic driver in subsets of lung cancer, and as a secondary driver of acquired resistance to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
284
3
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 324 publications
(296 citation statements)
references
References 73 publications
1
284
3
8
Order By: Relevance
“…Accordingly, the interaction between EGFR and MET in HNSCC cells may lead to resistance to anti‐EGFR antibodies . Indeed, efforts are underway to define the criteria for optimal use of a combination of MET and EGFR inhibitors wherein MET acts as a targetable co‐driver, particularly in EGFR‐mutant patients . In a study by Yang et al, HGF treatment of OSCC cell lines expressing high EGFR levels induced cetuximab resistance; however, treatment with Met inhibitor PHA‐665752 as well as MET siRNA was able to restore the sensitivity of OSCC cell lines to cetuximab.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the interaction between EGFR and MET in HNSCC cells may lead to resistance to anti‐EGFR antibodies . Indeed, efforts are underway to define the criteria for optimal use of a combination of MET and EGFR inhibitors wherein MET acts as a targetable co‐driver, particularly in EGFR‐mutant patients . In a study by Yang et al, HGF treatment of OSCC cell lines expressing high EGFR levels induced cetuximab resistance; however, treatment with Met inhibitor PHA‐665752 as well as MET siRNA was able to restore the sensitivity of OSCC cell lines to cetuximab.…”
Section: Discussionmentioning
confidence: 99%
“…3 MET amplification has been identified as a relevant molecular alteration in thoracic and upper abdominal cancers. 47 Indeed, multiple studies have demonstrated durable responses to MET inhibition among patients with MET -amplified cancers, including patients with CUP. 3,47 …”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] These alterations result in exclusion of exon 14 from the MET transcript, thus eliminating the Tyr1003 residue that mediates ubiquitination of the MET gene product hepatocyte growth factor receptor (HGFR). 5,6 As a result, proper degradation of HGFR protein is impaired, leading to enhanced oncogenic signaling. 4,7 Several published case reports have demonstrated clinical responses in patients with lung cancer positive for these variants to HGFR inhibitors (also referred to as MET inhibitors).…”
Section: Introductionmentioning
confidence: 99%